Direct and indirect relationships between Food Parental Practices, diet quality, and food satisfaction in adolescents - Del Valle, Carola; Miranda, Horacio; Orellana, Ligia; Adásme-Berrios, Cristian; Calvo-Porral, Cristina; Schnettler, Berta (Frontiers in Public Health, 2025)
IntroductionThe relationship between four parental feeding practices from the Comprehensive Feeding Practices Questionnaire for adolescents (CFPQ-Teen) and Satisfaction With Food-related Life (SWFoL) in adolescents was evaluated using diet quality measured using the Adapted Healthy Eating Index (AHEI) as a mediating variable.MethodsParticipants were 860 adolescents aged 10–16 years of both sexes who responded to four factors on the CFPQ-Teen, food satisfaction scale, and diet quality index. Structural equation analysis was used in a structural mediation model on a polychoric correlation matrix using the weighted least squares mean-variance adjusted (WLSMV) method.ResultsDiet quality was a mediating factor in the interaction between two parental practices related to parental modeling and adolescent control over SWFoL. There was evidence of a direct relationship between monitoring and restrictive factors for weight control and SWFoL.ConclusionsThe findings indicated that the association between parental feeding practices and food satisfaction may be direct or mediated by diet quality in adolescents.